2016
DOI: 10.1007/s11060-016-2297-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of matrix metalloproteinase type IV-collagenases in serum of patients with tumors of the central nervous system

Abstract: The basement membrane collagen IV-degrading matrix metalloproteinases -2 and -9 (MMPs) are most often linked to the malignant phenotype of tumor cells by playing a critical role in invasion, metastasis, angiogenesis, and vasculogenesis. We verified the activity of these two MMPs in the sera of patients affected by brain tumors (20 gliomas, 28 meningiomas and 20 metastasis) by zymography. The sera of 25 healthy volunteers with no concomitant illnesses were used for controls. Zymography showed four dominant gela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In addition, MMP-9 is an essential mediator of epithelial-mesenchymal transition, which is a key step in tumor progression and metastasis (43). The association between MMP-9 overexpression and the invasiveness of cancer has been reported in numerous studies (32,4447). In patients with PTC, positive MMP-9 staining is correlated with lymphatic spreading and the degree of tumor infiltration (3).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, MMP-9 is an essential mediator of epithelial-mesenchymal transition, which is a key step in tumor progression and metastasis (43). The association between MMP-9 overexpression and the invasiveness of cancer has been reported in numerous studies (32,4447). In patients with PTC, positive MMP-9 staining is correlated with lymphatic spreading and the degree of tumor infiltration (3).…”
Section: Discussionmentioning
confidence: 81%
“…MMPs have essential roles in various biological functions, including cell proliferation, differentiation, ECM degradation and remodeling, angiogenesis and cell migration. Furthermore, the expression and activity of MMP-9 are elevated in numerous types of human cancer (3234). In addition, the IHC positive staining of MMP-9 has been reported in 57.0–92.4% of patients with PTC (3,24).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of MMP levels in the sera of patients with primary and metastatic brain tumors demonstrated a significant increase in serum MMP‐9 levels when compared to healthy individuals. No significant difference was found for serum MMP‐2 levels (Ricci et al, ). mRNA expression of MMP‐9 was also identified as a prognostic biomarker that correlated with disease progression and survival in glioblastoma patients (Li et al, ).…”
Section: Diagnosis and Prognosis Of Cancers By Mmpsmentioning
confidence: 98%
“…from the same group, and some years later, did not find any correlation with serum MMP-9 levels and tumor size, survival or chemotherapy response, concluding that serum MMP-9 showed no utility in determining glioma disease status in a cohort of 111 GBM patients, and was not a clinically relevant prognostic marker of survival [54]. Ricci S et al tested a series of 60 brain tumors (20 gliomas, 20 meningiomas and 20 metastases) and 25 controls and showed that MMP-9 is significantly increased in the sera from patients with CNS tumors compared to healthy controls [55]. Again, this study had a very small number of patients of each tumor type to allow solid conclusions.…”
Section: Biomarkers Related To Vascular Proliferation and Cell Growthmentioning
confidence: 99%